2019
DOI: 10.3390/met10010019
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Deformation Induced Microstructure Refinement and Consequent Ultrahigh Toughness of a 20Mn2SiCrNi Bainitic Steel

Abstract: In this paper, we have studied the influence of deformation on the microstructure and mechanical properties of 20Mn2SiCrNi bainitic high strength steel processed through a hot rolling route. Simulation of different temperatures and degrees of deformation was carried out via Gleeble-1500. The study suggested that grain size is refined when the deformation is carried out at lower temperature (> Ac3). When the degree of deformation was increased from 20% to 60%, grain size and microstructure were both refined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…These characteristics suggested that the sintered 07Si03C steel microstructure could be termed as granular bainite [23]. The granular bainite was observed in some steels produced via continuous cooling [24,25] and one via hot rolling [26]. The microstructure given in Fig.…”
Section: Sintered 07si03c Steelmentioning
confidence: 94%
“…These characteristics suggested that the sintered 07Si03C steel microstructure could be termed as granular bainite [23]. The granular bainite was observed in some steels produced via continuous cooling [24,25] and one via hot rolling [26]. The microstructure given in Fig.…”
Section: Sintered 07si03c Steelmentioning
confidence: 94%